Simulation of strengthened reinforced concrete beam debonding behaviour using global energy balance approach / Nusrat Hoque - Nusrat , Hoque (2018)
Flaws and insufficient strength in the concrete-FRP interface normally initiate the debonding failure of FRP strengthened RC beams. Existing strength based model is generally good for predicting local failure of structure but not the overall failure. Hence, is not efficient in predicting the debonding failure. On the other hand, applications of finite element (FE) models require precise detail of the interface which is not always available. Fracture mechanic with global energy balance (GEBA) approaches seem to be more reliable for brittle material like concrete. A number of research works using this method for predicting debonding failure of externally bonded reinforcement (EBR) strengthened RC beams has been reported. The aim of this research work is to investigate the possibility of using GEBA based fracture mechanics model for beams strengthened using near-surface mounted (NSM) technique, combined NSM and EBR techniques, and prestressed FRP, beams that were precracked before strengthening, and T-beams. In addition, this thesis proposes an optimization design tool for the field applications of the model using the fuzzy approach and dimensional analysis for uncracked EBR-strengthened beams for end failure. The methodology involves finding available energy for the propagation of interface flaw in a beam using GEBA method. Debonding occurs when the available energy for interface flaw propagation reaches the fracture energy of the weakest material of the concrete-FRP composite system. The limiting fracture energy used for determining the failure state is the mode I fracture energy of the concrete because failure often occurs in the concrete substrate in a peeling nature. Different bond conditions, combination of two types of strengthening techniques, proper material modeling, equilibrium condition and geometry of beam are duly considered in the computation of energy dissipation. The outcome of the analysis is the critical FRP curtailment location from the beam support for end debonding and the critical debonded zone length debonding that initiates debonding in the vicinity of the highest moment. Parameters influencing debonding are reduced through grouping by dimensional analysis. Then, a fuzzy system is developed using the results of the parametric analysis of the model for the end debonding of EBR-strengthened beams. The validation using published experimental results demonstrates that the model is capable of predicting all modes of debonding failure for FRP strengthened RC beams, for any material and geometric properties of concrete beam, adhesive, FRP. The overall performance of the model is found to be satisfactory. The mean ratio between simulated to experimental failure loads for NSM strengthened beam are 0.99 and a standard deviation of 0.09. For hybrid strengthened beam the mean ratio and standard deviation are 0.95 and 0.09 respectively. For beams precracked before strengthening the mean ratio and standard deviation are 0.97 and 0.09. For beams strengthened using prestressed FRP the mean ratio and standard deviation are FRP 0.93 and 0.09. The mean ratio and standard deviation for T-beams are 0.94 and 0.07. The developed fuzzy dimensional analysis-based model also provides a good correlation with a coefficient of performance and relative error of 0.96 and 7.9%, respectively.